2020
DOI: 10.1007/s10856-020-06408-3
|View full text |Cite
|
Sign up to set email alerts
|

Material characterization and Streptococcus oralis adhesion on Polyetheretherketone (PEEK) and titanium surfaces used in implantology

Abstract: The aim of this study was to evaluate the interaction between Streptococcus oralis and Polyetheretherketone (PEEK), a novel material recently introduced in implantology. The topographical characterization and the Streptococcus oralis adhesion on this material were compared with other titanium surfaces, currently used for the production of dental implants: machined and double etched (DAE). The superficial micro-roughness of the PEEK discs was analyzed by scanning electron microscopy (SEM) and, the Energy Disper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
45
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(56 citation statements)
references
References 37 publications
5
45
0
Order By: Relevance
“…These findings indicate that PEEK also possesses good biocompatibility for MG-63 cells. With the combination of the verification results from this study and the data reported in the literature [ 42 , 43 ], it can be summarized that PEEK has anti-adhesive bacterial properties. With comparable MG-63 cell viability to Ti-6Al-4V and Y-TZP, PEEK is a suitable material for dental implants or abutment from a microbiological aspect.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…These findings indicate that PEEK also possesses good biocompatibility for MG-63 cells. With the combination of the verification results from this study and the data reported in the literature [ 42 , 43 ], it can be summarized that PEEK has anti-adhesive bacterial properties. With comparable MG-63 cell viability to Ti-6Al-4V and Y-TZP, PEEK is a suitable material for dental implants or abutment from a microbiological aspect.…”
Section: Discussionsupporting
confidence: 70%
“…As mentioned previously, the biofilm formation ability was related to hydrophilicity, surface roughness, and surface free energy. Although the present in vitro study did not consider PEKK, according to the previous report [ 42 , 43 ] it can be predicted that PEKK will have similar biological characteristics as PEEK. However, whether PEEK affects osteoblasts and their differentiation needs additional investigation.…”
Section: Discussionmentioning
confidence: 78%
“…Surface free energy has been shown to influence the adhesion of various cell types to dental materials [ 16 , 44 , 45 ]. Modifying surface free energy can have promoting or inhibiting effects on microbial adhesion, depending on the experimental conditions [ 46 , 47 , 48 ]. In an investigation on denture base and lining materials, an increase in surface free energy resulted in an increase in C. albicans adhesion [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the authors reported the lowest amount of bacterial contamination for the nano-roughness surface. It is well known in the literature that the micro-roughness surface rugophilia is a key factor for the induction of osteogenic actors' activity [49,50]. Several studies reported in animal experiments that implant micro-roughness is associated with higher bone-to-implant contact compared to machined implants [51][52][53][54].…”
Section: Discussionmentioning
confidence: 99%